The Construction Of An It Infrastructure For Knowledge Management - min Choe, Jong (Asian Academy of Management (AAM), 2016)
This study empirically investigated the relationships among the use of strategic performance measurement systems (SPMS), organisational learning, information systems (IS) strategic alignment, the information technology (IT) infrastructure for knowledge management (KM), competitive applications of knowledge resources, and organisational performance. The empirical data were collected from questionnaires and interviews with 117 sample firms. The collected data were statistically analysed with the statistical package for social science (SPSS). The results of this paper show that SPMS significantly and positively influences organisational learning and IS strategic alignment. The strategic communications and dialogues between the employees of an organisation, which are the mechanisms provided by SPMS, enhance the degrees of the IS strategic alignment. According to the results, it was observed that organisational learning and the IS strategic alignment have significant and positive effects on the construction of IT infrastructure for KM. Thus, the clear directions of IT development, which are formed with the integration between IS strategy and business strategy, seem to shape the goal orientations of the members in a firm and to enhance their collaborations in the construction of the IT infrastructure.